2022
DOI: 10.1016/j.cell.2022.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-ET of Env on intact HIV virions reveals structural variation and positioning on the Gag lattice

Abstract: Highlights d Structural analysis of immature HIV shows Env position on Gag hexameric rim d HIV Env has a flexible stalk that allows tilting and variation in stalk exposure d Env's fusion peptide is dynamic and exposed to solvent in membrane-bound Env d Glycans in unliganded Env shield antigenic sites and vary between protomers

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 101 publications
(187 reference statements)
2
34
0
Order By: Relevance
“…Whereas the largest isolate-specific differences in local structural dynamics were concentrated in the gp120 subunit, peptides in gp41 also exhibited structural differences in dynamics despite the relatively high sequence conservation of this subunit. The N -terminal fusion peptide of gp41 (peptide 1, Figure 4 ) was rapidly deuterated in all strains, in agreement with this region’s high degree of flexibility and solvent accessibility suggested by a lack of density in nearly all structures of unliganded Env ( Ananthaswamy et al., 2019 ; Kumar et al., 2019 ; Mangala Prasad et al., 2022 ). By contrast, the adjacent fusion peptide proximal region (FPPR, peptides 2 and 3; Figure 4 ) showed gradual deuterium uptake over 20 h, which suggests that it samples exposed conformations infrequently, and the extent of the dynamic sampling differed among isolates.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Whereas the largest isolate-specific differences in local structural dynamics were concentrated in the gp120 subunit, peptides in gp41 also exhibited structural differences in dynamics despite the relatively high sequence conservation of this subunit. The N -terminal fusion peptide of gp41 (peptide 1, Figure 4 ) was rapidly deuterated in all strains, in agreement with this region’s high degree of flexibility and solvent accessibility suggested by a lack of density in nearly all structures of unliganded Env ( Ananthaswamy et al., 2019 ; Kumar et al., 2019 ; Mangala Prasad et al., 2022 ). By contrast, the adjacent fusion peptide proximal region (FPPR, peptides 2 and 3; Figure 4 ) showed gradual deuterium uptake over 20 h, which suggests that it samples exposed conformations infrequently, and the extent of the dynamic sampling differed among isolates.…”
Section: Resultssupporting
confidence: 72%
“…Owing to intense immune pressures in each infected individual, Env evolves rapidly, making it the most variable part of the virus. Whereas high-resolution structures have provided a blueprint of Env’s protein and glycan architecture, the extent of Env structural and functional variation is only beginning to be understood ( Julien et al., 2013 ; Li et al., 2020 ; Mangala Prasad et al., 2022 ; Pancera et al., 2014 ; Struwe et al., 2018 ). One fundamental but poorly characterized feature of Env that impacts its immune recognition is the high level of intrinsic dynamics embodied in the trimer at equilibrium even before CD4 receptor activation ( Munro et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous cryo-EM study of Env protein in membrane-mimetic environments also observed tilting of Fab-bound Env, but interpreted the observed tilting to be mostly the result of Fab binding. 21 In contrast, a recent cryo-ET study of native HIV-1 virions published after completion of this work also found that Env proteins adopt different tilt angles relative to the virus membrane, 28 thus independently corroborating our single-particle cryo-EM and CGMD results that the Env protein undergoes tilting motions in the absence of bound antibody. In this regard, it is conceivable that coordination of the orthogonal docking to gp120 by the HIV-1 receptor CD4 and its co-receptor (CXCR4 or CCR5) 29 that prime and initiate conformational change required for gp160-mediated fusion, 30 respectively, pose challenges mitigated by ectodomain gesticulation.…”
Section: Discussionsupporting
confidence: 84%
“…1) and independent cryo-ET data. 28 These two findings contrast with those deduced from another cryo-ET study of HIV-1 BaL Env trimers on aldrithiol-2-inactivated viral particles, in which the MPER appears to form a stalk-like link between the Env ectodomain and the viral membrane. 31 The basis for this disparity is currently unknown.…”
Section: Discussionmentioning
confidence: 65%
“…Ultimately, the trimer transitions into its fully open, V3-loop crown and MPER-accessible conformation through splaying of the V1/V2 and V3 loops on either side of the gp120 subunit as seen in structures of CD4-17b-gp120/gp41 and CD4-CCR5-gp120 [ 11 13 , 18 ] (State D in Fig 9 ). How V1/V2- and V3-loop interactions are tied to MPER occlusion is currently unknown, but the splaying might increase Env flexibility, enhancing the ability of the trimer to tilt relative to the membrane (depicted in Fig 9 ) as observed in recent cryo-EM structures of Env trimers in viral membranes [ 81 ] and in artificial lipid bilayers bound to a single 10E8 antibody [ 82 ].…”
Section: Discussionmentioning
confidence: 99%